2015
DOI: 10.1021/co500152s
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented One-Pot Chemocontrolled Entry to Thioxoimidazolidinones and Aminoimidazolones: Synthesis of Kinase Inhibitor Leucettamine B

Abstract: A novel and highly chemoselective protocol for the construction of thioxoimidazolidinone and aminoimidazolone frameworks was explored, and the influence of the reaction conditions on product formation was studied to establish two distinct approaches for their selective formation. In this one-pot reaction, ambient temperature generally resulted in the formation of thioxoimidazolidinones, whereas microwave irradiation provided aminoimidazolones exclusively. An attempt to elucidate the observed chemoselectivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Leucettamine B was purified from the marine calcareous sponge Leucetta microraphis . Several synthesis protocols have been described for this natural product. Leucettamine B belongs to a family of natural products sharing a 2-aminoimidazolone ring structure found in several marine sponges . Despite its modest activity on DYRKs and CLKs (IC 50 values on DYRK1A and CLK4 = 1549 and 396 nM), the structure of Leucettamine B was the inspiration for the Leucettines and Leucettinibs (unpublished) chemical families.…”
Section: Discussionmentioning
confidence: 99%
“…Leucettamine B was purified from the marine calcareous sponge Leucetta microraphis . Several synthesis protocols have been described for this natural product. Leucettamine B belongs to a family of natural products sharing a 2-aminoimidazolone ring structure found in several marine sponges . Despite its modest activity on DYRKs and CLKs (IC 50 values on DYRK1A and CLK4 = 1549 and 396 nM), the structure of Leucettamine B was the inspiration for the Leucettines and Leucettinibs (unpublished) chemical families.…”
Section: Discussionmentioning
confidence: 99%
“…Structural variations at positions A, B, and C of the [6 + 5] heteroarylmethylene scaffold had considerable effects on the kinase inhibitory activity of the investigated compounds, in phase with their potential interaction within the ATP-binding pocket (see below). Clearly, the benzothiazol-6-ylmethylene (4, 19) and 6benzoxazol-6-ylmethylene (8, 23) heteroaryls followed by benzodioxol-5-ylmethylene (Leucettines) (3, 18), 2,3-dihydrobenzofuran-5-ylmethylene (9), and N2-methylated indazole-5ylmethylene (15,30) provided the most potent compounds. Methylation at position N3 (like in the natural product Leucettamine B (1)) reduced the potency of the compounds (Table 1, Table 2).…”
Section: ■ Resultsmentioning
confidence: 99%
“…During the screening of a library of >50 000 LMW heterocyclic compounds, in the search for inhibitors of the catalytic activity of recombinant DYRK1A, we identified Leucettamine B as a starting hit . Leucettamine B ( 1 ) is a natural substance purified from the marine calcareous sponge Leucetta microraphis (see refs and a review in ref ). Over 500 analogs/derivatives of Leucettamine B, collectively named Leucettines, have been synthesized and characterized in vitro. , One of them, Leucettine L41 ( 2 ), was used to demonstrate that a DYRK1A inhibitor rescued cognitive deficits associated with DS and AD. ,, More recently, a second-generation family of Leucettamine B analogs, Leucettinibs, has been developed. , Over 670 Leucettinibs have been synthesized, and the structure–activity relationship (SAR) has been described on the basis of 218 of these compounds. , One of the leads, Leucettinib-92, was extensively characterized in terms of selectivity, in silico modeling into the DYRK1A ATP-binding site, and cocrystallization with CLK1 …”
Section: Introductionmentioning
confidence: 99%
“…Since then, several other similar methods have been reported. 64,186,187 The most recently reported total synthesis of both leucettamines B and C was in 2017 by Dražić et al 111 Their synthesis is shown in Scheme 48 and starts with a β-lactam, which first reacts with N-(methylcarbamothioyl)benzamide and then undergoes a ring expansion under basic conditions to produce the desired imidazol-4-one. This was the first report of the total synthesis of leucettamine C. 97,190 In this synthesis (Scheme 49), a 2-azidoimidazole is converted to a 2-amino-4imidazolone through sequential oxidation and reduction after a number of alkylation steps.…”
Section: Polyandrocarpaminesmentioning
confidence: 99%